The impact of open science on science and technology activities and policy suggestions for Vietnam - Hai, Ha Cong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Open Science has been a topic of interest to scholars around the world for nearly two decades. Research results show that open science is a new approach to the scientific research process conducted through collaboration and a new way to spread knowledge widely and quickly based on digital technology platform. This article has analyzed and pointed out the positive impacts and challenges posed by open science on S&T activities, and evaluated the current situation of policies related to open science in Vietnam. On that basis, some suggestions on policies to promote the development of open science in Vietnam are proposed. Code: 21042001